2011
DOI: 10.1523/jneurosci.6684-10.2011
|View full text |Cite
|
Sign up to set email alerts
|

Essential Roles of Enteric Neuronal Serotonin in Gastrointestinal Motility and the Development/Survival of Enteric Dopaminergic Neurons

Abstract: The gut contains a large 5-HT pool in enterochromaffin (EC) cells and a smaller 5-HT pool in the enteric nervous system (ENS). During development, enteric neurons are generated asynchronously. We tested hypotheses that serotonergic neurons, which arise early, affect development/survival of later-born dopaminergic, GABAergic, nitrergic, and calcitonin gene-related peptide-expressing neurons and are essential for gastrointestinal motility. 5-HT biosynthesis depends on tryptophan hydroxylase 1 (TPH1) in EC cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
373
1
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 351 publications
(397 citation statements)
references
References 73 publications
18
373
1
3
Order By: Relevance
“…Li and colleagues studied Tph1−/−, Tph2−/− or double KOs to identify the role of neuronal vs nonneuronal 5-HT in the gut. 42 Their results were quite surprising and revealed that peripheral 5-HT (Tph1-derived 5-HT: ∼95% of gut 5-HT content) has only a very minor role in regulation of GI motility in the mouse, while neuronal (Tph2 derived 5-HT: ∼5% of gut 5-HT content) has a much more considerable role than previously believed. Tph1 KO mice did not differ from controls in GI functions measured (gastric emptying, total intestinal transit, and colonic motility.…”
Section: ■ Tph1-derived Serotonin In the Gut: What Does It Really Do?mentioning
confidence: 96%
See 1 more Smart Citation
“…Li and colleagues studied Tph1−/−, Tph2−/− or double KOs to identify the role of neuronal vs nonneuronal 5-HT in the gut. 42 Their results were quite surprising and revealed that peripheral 5-HT (Tph1-derived 5-HT: ∼95% of gut 5-HT content) has only a very minor role in regulation of GI motility in the mouse, while neuronal (Tph2 derived 5-HT: ∼5% of gut 5-HT content) has a much more considerable role than previously believed. Tph1 KO mice did not differ from controls in GI functions measured (gastric emptying, total intestinal transit, and colonic motility.…”
Section: ■ Tph1-derived Serotonin In the Gut: What Does It Really Do?mentioning
confidence: 96%
“…Tph1 KO mice did not differ from controls in GI functions measured (gastric emptying, total intestinal transit, and colonic motility. 42 In comparison, Tph2 KO animals had major changes in each function and the double KOs were indistinguishable from Tph2-null mice. The results of Li et al indicate that Tph1-derived 5-HT is trivial for normal GI motility.…”
Section: ■ Tph1-derived Serotonin In the Gut: What Does It Really Do?mentioning
confidence: 96%
“…[132][133][134] One of the key signaling pathways is via TLR expressed in immune cells of the bowel wall and the neurons of the ENS representing a mechanism for the microbiota to communicate with the CNS. 76 The TLR are pattern recognition receptors detecting lipopolysaccarides (membrane-component of Gram-negative bacteria) and other molecules of microbial origin.…”
Section: Gut-brain Signaling -The Gut Brain Axismentioning
confidence: 99%
“…5,14 Lewy pathology and dopaminergic neuron loss also has been found in the enteric nervous system of many PD patients, particularly the lower gastrointestinal tract, which might be responsible for decreased gastric motility and constipation. 15,16 The inevitability of enteric nervous system pathology in PD has been challenged, however. [17][18][19] These studies show that enteric nervous system Lewy pathology is a frequent, but not necessary concomitant of PD.…”
Section: Introductionmentioning
confidence: 99%